Respostas
respondido por:
1
Vamos lá:
x^2 -4x -32 = 0
a = 1. b = -4. c = -32
Delta = b^2 -4ac
Delta = -4^2 -4*1*-32
Delta = 16 + 128
Delta = 144
x = (-b +- Raiz quadrada de Delta)/2a
x = (4 +- 12)/2
x' = (4+12)/2
x' = 16/2
x' = 8
x'' = (4-12)/2
x'' = -8/2
x'' = -4
S = {(-4;1)}
Dúvidas ?
Seguem os comentarios...
-Expertiee
x^2 -4x -32 = 0
a = 1. b = -4. c = -32
Delta = b^2 -4ac
Delta = -4^2 -4*1*-32
Delta = 16 + 128
Delta = 144
x = (-b +- Raiz quadrada de Delta)/2a
x = (4 +- 12)/2
x' = (4+12)/2
x' = 16/2
x' = 8
x'' = (4-12)/2
x'' = -8/2
x'' = -4
S = {(-4;1)}
Dúvidas ?
Seguem os comentarios...
-Expertiee
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás